2015
DOI: 10.1016/j.jim.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based production of two chimeric monoclonal IgG antibodies directed against immunodominant epitopes of Vibrio cholerae lipopolysaccharide

Abstract: We have produced and characterized two chimeric IgG1 monoclonal antibodies that bind different immunodominant epitopes on Vibrio cholerae lipopolysaccharide (LPS). MAb 2D6 IgG1 recognizes Ogawa O-polysaccharide antigen, while mAb ZAC-3 IgG1 recognizes core/lipid A moiety of Ogawa and Inaba LPS. Both antibodies were expressed using a Nicotiana benthamiana-based rapid antibody-manufacturing platform (RAMP) and evaluated in vitro for activities associated with immunity to V. cholerae, including vibriocidal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 29 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…The plates were incubated at 37°C and the diameter of bacterial migration away from the point of inoculation was determined at 4 and 8 h time points. When treated with PBS or an isotype antibody control, V. cholerae strain O395 had a migration diameter of ~0.8 cm at 4 h and 1.5 cm at 8 h. In the presence of ZAC-3 IgG, bacterial migration was reduced 4–10 fold (Figure 1Ai), which is consistent with our previous results [15]. The motility studies were then repeated with the El Tor Inaba strain C6706.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The plates were incubated at 37°C and the diameter of bacterial migration away from the point of inoculation was determined at 4 and 8 h time points. When treated with PBS or an isotype antibody control, V. cholerae strain O395 had a migration diameter of ~0.8 cm at 4 h and 1.5 cm at 8 h. In the presence of ZAC-3 IgG, bacterial migration was reduced 4–10 fold (Figure 1Ai), which is consistent with our previous results [15]. The motility studies were then repeated with the El Tor Inaba strain C6706.…”
supporting
confidence: 88%
“…However, we recently reported that ZAC-3, a monoclonal antibody against the core/lipid A region of V. cholerae O1 LPS, abolishes migration of V. cholerae O1 strain O395 in a semi-solid agar motility assay, an observation that may have a number of implications for cholera vaccine development [15]. ZAC-3 was first isolated as a monoclonal IgA from a B cell hybridoma derived from mouse Peyer’s patches [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of greater amounts of Sal4 further reduced the CI with a maximal reduction occurring at concentrations above 1.2 μg Sal4 IgA. Invasion of Peyer's patch tissues by AR05 and AR04 was unaffected by 2D6, an anti-Vibrio cholerae IgA mAb that served as the isotype control for these studies [13,21].…”
Section: Oral Administration Of Sal4 Iga Prevents Infection Of Stm Inmentioning
confidence: 91%
“…For the soft agar motility assays, LB medium with 0.3% Bacto agar (Becton Dickinson) was prepared with 15 μg/ml of each mAb of interest poured into 60 mm Petri dishes (n = 3 per treatment group) and allowed to set at room temperature for 30 min. Individual colonies of ATCC 14028 STm were then picked from a freshly-streaked LB agar plate and stabbed directly into the center of the plate [21]. The plates were placed in a 37˚C incubator and the diameters of the concentrically growing bacterial cultures were measured at 60-minute intervals.…”
Section: Soft Agar Motility Assaysmentioning
confidence: 99%